Analisis Miskonsepsi Siswa Pada Materi Pengukuran Di SMAN 1 Grati Menggunakan CRI (Certainty Of Response Index) - Sari, Agung Suci Dian; A, Ruslimin; Safitri, Umi Nur; Anam, Khoirul (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze students' misconceptions on material measurement using CRI (Certainty Of Response Index). This research was conducted at SMAN 1 Grati in the odd semester of 2021 in class X MIPA 5 and X MIPA 6. This research method is descriptive quantitative. Based on the research, it was found that overall students' misconceptions were still very low, reaching 16.5%. The students' misconceptions are caused by, among other things, making the wrong quantity, students not understanding the quantities that work on a measurement, students understanding wrong intuition because they rarely observe or experiment on measurements directly and also because learning is carried out online